2020
DOI: 10.35787/jimdc.v9i4.460
|View full text |Cite
|
Sign up to set email alerts
|

Mucoepidermoid Carcinoma: A Demographic and Histopathological Profile

Abstract: Background: To find the frequency and clinico-pathological presentation of mucoepidermoid carcinoma (MEC).Materials and Methods:In this study, we included all the malignant salivary gland tumors. Among these the frequency of mucoepidermoid carcinoma was considered. Age, gender, histopathological grading and anatomical site of tumor were included in data analysis.Results:Out of 60 malignant salivary gland tumors reported to the histopathology department, 30 tumors were diagnosed as mucoepidermoid carcinomas. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…Though there are studies where there is no significant difference is observed, but the results remained inconsistent (8). Mucoepidermoid type was predominant in our series, this was consistent with other studies (9). Other studies have also reported the same with second most common histological types being adenoid cystic carcinoma (6).…”
Section: Figure 1 Age Distribution Of Patients Presenting With Saliva...supporting
confidence: 79%
“…Though there are studies where there is no significant difference is observed, but the results remained inconsistent (8). Mucoepidermoid type was predominant in our series, this was consistent with other studies (9). Other studies have also reported the same with second most common histological types being adenoid cystic carcinoma (6).…”
Section: Figure 1 Age Distribution Of Patients Presenting With Saliva...supporting
confidence: 79%
“…Recently a study was conducted in Armed Forces Institute of Pathology on 30 cases of MEC and it was reported that low grade MEC was most common tumor similar to result of this study. 28 There was certain limitation of the current study, which might be the cause of differences in results while comparing with other studies. Malignant salivary gland tumors are rare, therefore the sample size in the current study was small (n=55) so, it was difficult to evaluate the definitive role of Bcl-2.…”
Section: Discussionmentioning
confidence: 75%